NTHi killing activity is reduced in COPD patients and is associated with a differential microbiome - Vancheswaran Gopalakrishnan; Ben Sparklin; Jung Hwan Kim; Jerome Bouquet; Margaret Kehl; Tara Kenny; Christopher Morehouse; Carolina Caceres; Paul Warrener; Ventzislava A. Hristova; Susan Wilson; Harini Shandilya; et al. (Respiratory Research)
Abstract Chronic obstructive pulmonary disease (COPD) is a chronic lung disease characterized by airway obstruction and inflammation. Non-typeable Haemophilus influenzae (NTHi) lung infections are common in COPD, promoting frequent exacerbations and accelerated lung function decline. The relationship with immune responses and NTHi are poorly understood. Herein, we comprehensively characterized the respiratory microbiome and mycobiome of patients while investigating microbial dynamics and host immune changes attributable to NTHi killing activity. Mild-to-moderate COPD patients encompassing frequent and infrequent exacerbators and healthy volunteers (HV) were enrolled. Microbial composition, proteomics and NTHi killing activity was analyzed using bronchoalveolar lavage fluid (BALF). In addition, antigen–antibody titers in sera to COPD pathogens were determined using a multiplex assay. Differential abundance analysis revealed an enrichment of Actinobacteria and Bacteroidetes in the BALF of COPD and HV subjects respectively. Significant differences in the IgA titer response were observed against NTHi antigens in COPD vs. HV. Notably, there was also significantly greater killing activity against NTHi in BALF from COPD vs. HV subjects (OR = 5.64; 95% CI = 1.75–20.20; p = 0.001). Stratification of COPD patients by NTHi killing activity identified unique microbial and protein signatures wherein Firmicutes, Actinobacteria and haptoglobin were enriched in patients with killing activity. We report that differences in host immune responses and NTHi-killing activity are associated with microbiome changes in mild-to-moderate COPD. This is suggestive of a potential link between the respiratory microbiome and immune activity against NTHi in the context of COPD pathogenesis even at this disease stage.